If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + c) = 2(c + -7) (3 * 3 + c * 3) = 2(c + -7) (9 + 3c) = 2(c + -7) Reorder the terms: 9 + 3c = 2(-7 + c) 9 + 3c = (-7 * 2 + c * 2) 9 + 3c = (-14 + 2c) Solving 9 + 3c = -14 + 2c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-2c' to each side of the equation. 9 + 3c + -2c = -14 + 2c + -2c Combine like terms: 3c + -2c = 1c 9 + 1c = -14 + 2c + -2c Combine like terms: 2c + -2c = 0 9 + 1c = -14 + 0 9 + 1c = -14 Add '-9' to each side of the equation. 9 + -9 + 1c = -14 + -9 Combine like terms: 9 + -9 = 0 0 + 1c = -14 + -9 1c = -14 + -9 Combine like terms: -14 + -9 = -23 1c = -23 Divide each side by '1'. c = -23 Simplifying c = -23
| k-2k+-7k=-18 | | 5x+21+3x=29 | | 10-2r=28 | | 3(n+1)-(7n-5)=-5n | | 2.33=(x-78)/3 | | 4+8=6+g | | a-18=7a | | 2(0)+0-3(0)+4= | | 0.11p+1.25y=8.62 | | 15t+-13t+-15=-19 | | 10v=-6 | | 4(x+9)=7+3x | | 2x-1+-2x^2=0 | | m^2-18m+73=-4 | | 65+2x= | | 16q-9q-2q-4q+3q=20 | | 3X+3+72=90 | | 9(y+4)=8y | | 4y^2+y-6=0 | | 70+1x=8x | | 8v+4v-v-7v=12 | | 3X+3+72=180 | | 6(x-9)=6+7x | | (9p^4+7p^3-2)+(6p-5p+6)= | | 1/k^2=0.25 | | -6v-20=-6v+21 | | 17x+504= | | (3n-4)+n=28 | | 116=4(-1+6m) | | 14r+4r-18r+2r+3r=10 | | 3.00x=-9 | | 2(6x-5)+22= |